A novel c.1759T>G variant in follicle-stimulating hormone-receptor gene is concordant with male determination in the flathead grey mullet (Mugil cephalus). Issue 2 (24th December 2020) - Curzon, Arie Y; Dor, Lior; Shirak, Andrey; Meiri-Ashkenazi, Iris; Rosenfeld, Hana; Ron, Micha; Seroussi, Eyal
Abstract: Various master key regulators (MKRs) that control a binary switch of sex determination (SD) have been found in fish; these provide an excellent model for the study of vertebrate genetic SD. The SD region in flathead grey mullet has been previously mapped to a 1 Mbp region harboring 27 genes, of which one is follicle-stimulating hormone receptor ( fshr) . Although this gene is involved in gonad differentiation and function, it has not been considered as an MKR of SD. We systematically investigated polymorphism in mullet fshr using DNA shotgun sequences, and compared them between males and females. Capable of encoding nonconservative amino acid substitutions, c.1732G>A and c.1759T>G exhibited association with sex on a population level ( N = 83; P ≤ 6.7 × 10 −19 ). Hence, 1732 A and 1759 G represent a male-specific haplotype of the gene, designated as " fshry. " Additional flanking SNPs showed a weaker degree of association with sex, delimiting the SD critical region to 143 nucleotides on exon 14. Lack of homozygotes for fshry, and the resulting divergence from Hardy–Weinberg equilibrium ( N = 170; P ≤ 3.9 × 10 −5 ), were compatible with a male heterogametic model (XY/XX). Capable of replacing a phenylalanine with valine, c.1759T>G alters a conserved position across the sixth transmembrane domain of vertebrate FSHR s. Amino acid substitutions in this position in vertebrates are frequently associated with constant receptor activation and consequently with FSH / FSHR signaling alteration; thus, indicating a potential role of fshr as an MKR of SD.